2016
DOI: 10.1002/pssr.201510443
|View full text |Cite
|
Sign up to set email alerts
|

Contacting boron emitters on n-type silicon solar cells with aluminium-free silver screen-printing pastes

Abstract: In the production of n‐type Si solar cells, B diffusion is commonly applied to form the p+ emitter. Up to now, Ag screen‐printing pastes, generally used to contact P emitters, had been incapable of reliably contact B emitters. Therefore, a small amount of Al is generally added to Ag pastes to allow for reasonable contact resistances. The addition of Al, however, results in deep metal spikes growing into the Si surface that can penetrate the emitter. Losses in open‐circuit voltage are attributed to these deep m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Thus, the poorer poly-Si/SiO x contact passivation on a textured surface is observed for boron-doped and not phosphorous-doped contacts. This suggests that the poor passivation of the boron-doped poly-Si/SiO x contact on a textured surface is likely related to a boron−SiO x interaction, 25,26 or a high defect density created because of emitter formation, 27 rather than only poorer SiO x /c-Si interfacial passivation of a predominantly Si(111) faceted textured surface. 10,20,21 Similar observation has also been made for the pinhole-type poly-Si/ SiO x contacts on a textured surface.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the poorer poly-Si/SiO x contact passivation on a textured surface is observed for boron-doped and not phosphorous-doped contacts. This suggests that the poor passivation of the boron-doped poly-Si/SiO x contact on a textured surface is likely related to a boron−SiO x interaction, 25,26 or a high defect density created because of emitter formation, 27 rather than only poorer SiO x /c-Si interfacial passivation of a predominantly Si(111) faceted textured surface. 10,20,21 Similar observation has also been made for the pinhole-type poly-Si/ SiO x contacts on a textured surface.…”
Section: Resultsmentioning
confidence: 99%
“…Different sizes of crystallite imprints can be observed; however, their estimated maximum penetration depths are less than about 80 nm. Hence, they are significantly smaller in size then those commonly observed for Ag‐Al contacts . Apparently, the number of imprints is significantly larger for the sample in Figure (a), which shows the lower ρ C ≈ 1.5 mΩ cm 2 in comparison with the sample in Figure (b) with the higher ρ C ≈ 7.5 mΩ cm 2 .…”
Section: Resultsmentioning
confidence: 70%
“…These improvements revived the approach to use pure Ag pastes (without Al) for contacting boron‐doped surfaces. Initial results demonstrate that these state‐of‐the‐art Ag pastes are indeed also capable of contacting boron‐doped surfaces with ρ C in the single‐digit range . It has been reported that the volume of the contact body (finger) can have an impact on the contact formation during the firing process: the higher the volumes (i.e., the larger the finger widths) are, the lower are the measured ρ C values …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some reports have proved that the contact resistivity between the electrode and the Si substrate could be remarkably reduced by adding aluminum particle to the Ag paste to form silver-aluminum (Ag-Al) paste [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. On the other hand, with the presence of the Al particle, some inappropriate Ag/Al spikes can give birth to a larger dark saturation current beneath the paste contact area [ 25 , 26 , 27 ]. Lago’s group proved that the spiking problem could be solved by adding silicon powder to the metallization paste [ 23 ].…”
Section: Introductionmentioning
confidence: 99%